How Internet of Things changes business model of Microsoft OEM team - Hruška, Jan; Andera, Michal, 1984-; Urbík, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
The main goal of this thesis is to discover how an emerging technological megatrend, the Internet of Things, changes the business model of the Microsoft OEM team. OEM business is fully dependent on sales of Windows licenses; however, the PC market is declining and whole Microsoft is shifting into offering of cloud services while being financed by the OEM revenues. Nevertheless, the strategy of how the OEM team fits into the future of cloud offerings is clearly missing. To discover what changes should be made inside the current business model, 13 interviews with managers across Microsoft were conducted and analyzed. Identified themes were assigned to business model building blocks, ranked by the importance, and supported by relevant quotes from interviews as well as the theoretical background. The most important subjects of changes were identified as partners, activities and value proposition; however, changes will be seen in every aspect of the OEM business. As a result, specific changes in building blocks are described and the first steps towards the Internet of Things strategy suggested. That will ensure the relevance of the conservative OEM team in the connected future.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses